Study of field training program to improve the successful of the department of P.E at the University of Soran to prepare student - Abdul rahman, Mazin; Elias, Eman (Journal of Physical Education, 2013)
-the aim of the study is to know the effect of the field training program to improve the abilities of student to develop the physical Fitness of the secondary school student -the effect of physical education department programs university of soran to prepare its student to teach physical education -the researchers used a survey method the sample consist of 41 student which selected randomly the result shows the effect of field training program and the successful of the department of P.E to choose its program for their student .